2019
DOI: 10.3390/nu11123056
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Own Mothers’ Milk Fortification Protocol Affect Early Plasma IGF-I and Ghrelin Levels in Preterm Infants. A Randomized Clinical Trial

Abstract: The aim was to investigate the effect of two own mother’s milk (OMM) fortification protocols on (a) IGF-I and ghrelin plasma levels at 35 post-conceptional weeks (PCW, T2) and whether this effect is maintained after elimination of the differences in OMM fortification, and (b) growth until 12 months corrected age. Forty-eight OMM-fed preterm infants (GA 24–32 weeks) were randomly allocated to the fixed-fortification (FF) group (n = 23) and the protein-targeting fortification (PTF) group (n = 25) targeting the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…One study found no differences in growth or body mass index from 40 weeks to 12 months corrected age. 12…”
Section: In -Hos Pital Individualis Ed Multi -N Utrient Fortifi C Ati Onmentioning
confidence: 99%
“…One study found no differences in growth or body mass index from 40 weeks to 12 months corrected age. 12…”
Section: In -Hos Pital Individualis Ed Multi -N Utrient Fortifi C Ati Onmentioning
confidence: 99%
“…Targeted values for the macronutrient and energy content of enteral feeds are typically based on consensus recommendations for preterm infants, including 3.5-4.5 g/kg/day protein, 4.8-6.6 g/kg/day lipids, 11.6-13.2 g/kg/day carbohydrates, 110-135 kcal/kg/day, and protein/energy ratios of 3.2-4.1 g/100 kcal [2]. Fortification may be achieved through a combination of multicomponent fortifiers, as well as specific modular macronutrient products such as medium-chain triglycerides, safflower oil, whey protein, casein-based liquid protein, maltrodextrin, and glucose polymers [43,[45][46][47][48][49]. A human-milk-derived cream fortifier is also commercially available to provide additional fat, protein, and carbohydrate content [45].…”
Section: Individualized Fortificationmentioning
confidence: 99%
“…A human-milk-derived cream fortifier is also commercially available to provide additional fat, protein, and carbohydrate content [45]. The frequency of human milk analysis in studies of targeted fortification has ranged from twice daily to weekly [43,45,46,[48][49][50]. In a study evaluating the effects of differing sampling intervals ranging from daily to weekly, Rochow et al found that twice weekly milk analysis achieved macronutrient intake within 5% of targeted goals [50].…”
Section: Individualized Fortificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Current literature indicates that nutrition in early life is associated with long-term growth and neurodevelopment. Among preterm and LBW infants, an HM-based diet may reduce morbidity and mortality [6][7][8][9]. However, HM alone is insufficient to meet the nutritional needs of preterm and LBW infants at regular feeding volumes [10].…”
Section: Background and Rationalementioning
confidence: 99%